The Spillover of the ‘Border Spectacle’ into Schools: Undocumented Youth, Media Frames, and the School-to-Deportation Pipeline - Eric Macias; Laura Singer (Youth)
This article examines how media outlets create a “border spectacle” (De Genova 2013) in schools, which contributes to the criminalization and deportability of undocumented immigrant students. Using content analysis, we studied n = 30 news articles that covered an incident in 2017 where two undocumented young men were accused of sexual assault and rape of a young woman in the school they all attended. This paper builds on the “school-to-deportation pipeline” by suggesting that, in addition to the zero-tolerance behavioral policies established by schools and teacher’s racist behaviors, the media coverage of alleged criminal acts also play a role in the expulsion and criminalization of undocumented students. The analysis of the news articles highlights four types of media frames employed to criminalize the young men involved in the case prior to these allegations being addressed by a court of law: (1) immigrant youth as sexual predators; (2) immigration as a correlation to a criminal act; (3) parents as the real victims of the case; and (4) sexual assault victims as collateral damage. Each of these media frames are built on xenophobic tropes that have historically facilitated the marginalization of Black and Latinx people, but in this case, it specifically targets undocumented young men. Collectively, the four media frames exemplify how media create a “border spectacle” in schools, manufacturing a moral hysteria to further marginalize and criminalize undocumented youth. We argue that, as a result of schools becoming border spectacles, undocumented young people’s fear of feeling targeted based on their “illegality” is intensified, and their sense of inclusion is hindered in an often thought to be safe and inclusive space for undocumented young people.